A mass mortality of fishes caused by receding water levels in the vegetated littoral zone of the West Kleinemonde Estuary, South Africa. Issue 2 (25th June 2018) - Whitfield, AK; Cowley, PD
Abstract : On 15 November 2017 the mouth of the West Kleinemonde Estuary breached following heavy catchment rains and increased river flow. The water level in the estuary following mouth opening decreased by 1.65 m within 24 h, resulting in an almost complete draining of the littoral zone where large beds of the aquatic macrophyte Ruppia cirrhosa and mats of the associated filamentous algae were present. As the water depth within the plant beds decreased, the macrophytes, together with the algal filaments, created an increasingly dense mat, trapping fish that were resident, foraging or passing through the littoral zone. By 16 November 2017 large numbers of fishes belonging to at least 20 species were trapped in pools and depressions within the littoral, as well as within the R. cirrhosa beds and filamentous algal mats in the lower reaches of this system. Other affected taxa included crustaceans, especially isopods, and large numbers of small bivalves attached to macrophyte vegetation. Beneficiaries of the fish kill, in terms of unexpected food availability, included a variety of piscivorous bird species and the Cape clawless otter Aonyx capensis . This is the first documented account of a diverse species fish kill associated with estuary mouth breaching.